Gendered Perspectives on Omnichannel Marketing in Micro and Small and Medium Enterprises (MSMEs): A Pilot Study of Northern Sri Lanka - Sumangala, F.; Dilogini, S. (University of Jaffna, 2024)
Purpose: This pilot study examines the gender-based differences in omnichannel marketing strategies among micro, small, and medium enterprises (MSMEs) in the Northern Province of Sri Lanka. Understanding how gender influences these approaches is essential for the success and sustainability of entrepreneurs, as it can highlight unique challenges and opportunities faced by men and women. By exploring these differences, the study aims to contribute valuable insights for promoting inclusive and effective marketing practices in the MSME sector. Methodology: The study employs a qualitative research design to explore gender differences in omnichannel marketing. Data were gathered through in-depth interviews with ten entrepreneurs from MSMEs in the Northern Province, comprising five men-led and five women-led enterprises. The selected participants actively use at least one digital marketing platform and operate physical outlets, making them suitable for exploring the integration of digital and physical marketing channels. This purposive sampling ensures a balanced gender representation and captures diverse experiences for a comparative analysis. Findings: The findings reveal significant gender differences in omnichannel marketing approaches among MSMEs in Northern Province, Sri Lanka. Women entrepreneurs often lack awareness and resources, leading them to rely on existing business models and customer relationships. In contrast, men entrepreneurs show greater interest in adopting omnichannel strategies, inspired by examples of success, but remain cautious about potential costs and management challenges. Research limitation: This pilot study focuses on a small sample of only ten entrepreneurs (5 men and 5 women), which may not provide a comprehensive view of gender differences in omnichannel marketing practices among all MSMEs in Northern Province, Sri Lanka. In-depth interviews offer rich insights, they are subjective and may not capture the full range of experiences and perspectives. Implication: The findings can provide insights into how gender influences marketing strategies and consumer engagement. Women and men may approach omnichannel marketing differently, reflecting their unique experiences, challenges, and perspectives. By documenting the experiences of women and men entrepreneurs, the study can empower others in the community, providing role models and practical examples of successful omnichannel marketing practices.
Keywords: Digital Marketing; Gender; MSMEs; Northern Province Sri Lanka; Omnichannel marketing